Possibilities of branding the pork in Croatia – review - Budimir, Kristina; Djurkin, Ivona; Lukic, Boris; Dzijan, Snjezana; Margeta, Vladimir; Kušec, Goran (Acta Agraria Kaposváriensis, 2014)
Black Slavonian pig is an indigenous pig breed black in colour, resistant and convenient for keeping in extensive conditions. It is also characterized by good meat quality, suitable for typical traditional meat products. Traditionally produced food came into the focus which led to more often use of geographical indications as the valuable rural development strategy. Since Black Slavonian pig is a late maturing breed with low lean meat content, meat processors often use the meat of modern pig breeds in the production of traditional products. Molecular identification of breed is a good tool for authentication of meat. Since age and sex are among the most significant sources of variation of the carcass and meat quality traits in pigs, the research on the optimal time for slaughter with respect to these factors could increase the profitability of pork production. The genetic influence on meat quality traits is nowadays well described by the use of molecular markers and candidate genes such as IGF2, MC4R, H-FABP3 and LEPR; their frequencies could be of assistance in the description of Black slavonian pig and its exceptional meat quality traits. The investigation of sensory characteristics and chemical analysis of meat and meat products is needed to determine the typical physicochemical characteristics and sensory profile of pork originated from Black Slavonian Pig which is a firm base for branding. Finally, DNA characterisation of the breed can be used as the tool for authentication of pork in the aim of preventing possible adulterations of autochthonous meat products.